Prevalence of depressive symptoms among young adults in Brazil: Results of the 2013 and 2019 editions of the National Health Survey - Bruno Luciano Carneiro Alves de Oliveira; Fabiana Alves Soares; Priscila de Souza Aquino; Patrícia Neyva da Costa Pinheiro; Gilberto Sousa Alves; Ana Karina Bezerra Pinheiro (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To estimate the prevalence of depressive symptoms in the population aged 18 to 24, according to socioeconomic and demographic aspects in Brazil, comparing its evolution between 2013 and 2019. Methods: Cross-sectional study carried out with secondary data obtained from National Health Survey 2013 and 2019. It were included 7,823 young adulthood (aged 18 to 24) from 2013 and 8,047 from 2019. The instrument used to assess depression was the Patient Health Questionnaire-9 (PHQ-9). All estimates included population weights and complex sampling. Results: The prevalence of depression almost doubled: 10.9% (95%CI 9.6-12.2) in 2019, compared to 5.6% (95%CI 4.8-6.4) in 2013, an absolute difference of 5.3% (4.5-6.0) greater. Women were the most affected in both surveys, with an increase between 2013 (8.3%; 95%CI 6.9-9.6) and 2019 (15.6%; 95%CI 13.5-17.6) higher than that of men (2013: 2.9%; 95%CI 2.0-3.8 and 2019: 6.2%; 95%CI 4.7-7.7). In both sexes, the pattern of increase was greater for the groups aged 18 to 20, not participating in religious activities, who were at the lowest levels of education and income, who lived with two or three or more people, who lived in the Northeast, Southeast, capitals and metropolitan areas of the country. Conclusion: There was a significant increase in the prevalence of depressive symptoms over the six years between the two surveys. However, this increase did not occur homogeneously among the characteristics analyzed, indicating population groups and locations in Brazil where the presence of these symptoms increased most in the period.